2015
DOI: 10.1590/s2179-975x0114
|View full text |Cite
|
Sign up to set email alerts
|

Wetland nutrient retention and multitemporal growth – Case study of Riacho Fundo’s Wetland

Abstract: Aim: The aim of this research was to evaluate the nutrient retention of Riacho Fundo’s wetland in controlling Lake Paranoá (Brasilia, Brazil) eutrophication analyzing its ability to retain nitrogen and phosphorus. Furthermore, the article aimed at verifying the multitemporal growth rate of Riacho Fundo’s wetland. Methods Five sampling points were distributed along the wetland, from its beginning to its outflow into Lake Paranoá. Twenty-five field campaigns during periods of drought and rain from November 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is also noted that Total Phosphorus values were higher in rainy seasons compared to the drier period (Figure 13). In the study conducted by Dias & Baptista [9] in the wetland area of Riacho Fundo, Brasília, Brazil, an average retention of 34% for TP between the inlet and outlet points analyzed by the authors was observed. After an extensive literature review on nutrient removal in wetlands, Fisher and Acreman [12] identified that 84% of the studied wetlands showed Phosphorus retention, 10% indicated an increase in Phosphorus, and in 6% of the studied areas, there was no difference between the input and output of wetlands.…”
Section: Total Phosphorus Assessmentmentioning
confidence: 90%
See 2 more Smart Citations
“…It is also noted that Total Phosphorus values were higher in rainy seasons compared to the drier period (Figure 13). In the study conducted by Dias & Baptista [9] in the wetland area of Riacho Fundo, Brasília, Brazil, an average retention of 34% for TP between the inlet and outlet points analyzed by the authors was observed. After an extensive literature review on nutrient removal in wetlands, Fisher and Acreman [12] identified that 84% of the studied wetlands showed Phosphorus retention, 10% indicated an increase in Phosphorus, and in 6% of the studied areas, there was no difference between the input and output of wetlands.…”
Section: Total Phosphorus Assessmentmentioning
confidence: 90%
“…This is due to water infiltration through saturated layers of anoxic organic sedimentary material and plant debris with high denitrification potential, so that high denitrification rates are common in wetlands and riparian zones rich in organic matter [41]. Dias & Baptista [9] also observed the reduction of TN in the wetland area of Riacho Fundo, Brasília, Brazil. The authors found an average retention of 36.7% for TN between the inlet and outlet of the wetland area.…”
Section: Total Nitrogen Assessmentmentioning
confidence: 98%
See 1 more Smart Citation